Impresje Warszawskie : Fotografowie Warszawy Swojej Stolicy. (Warszawa : Galeria Zacheta, 1989)
Andrzejewski, Andrzej ; Bilinski, Tadeusz ; Charewicz, Lech ; Cieslak, Mieczyslaw H. ; Fitak, Stanislaw ; Garnuszewska, Antonina ; Grochowicz, Edward ; Hartwig, Edward ; Fijalkowska, Ewa Hartwig - ; Hartwig, Helena ; Jablonski, Krzysztof ; Jalosinski, Aleksander ; Jaskiewicz, Jan ; Kaczkowski, Adam ; Kapuscik, Zbigniew ; Kowalski, Tadeusz ; Kupiecki, Edmund ; Siemaszko, Zbyszko ; Sobolewski, Aleksander ; Stoklosa, Leszek ; Suminski, Tadeusz ; Syndoman, Stanislaw ; Swiatek, Zygmunt ; Swiecki, Lucjan ; Weselik, Jan ; Wolinski, Janusz ; Zborski, Andrzej ; Zielinski, Wieslaw
Impresje Warszawskie : Fotografowie Warszawy Swojej Stolicy, 150 lat fotografii, Galeria Zacheta, Warszawa, styczen (January) 1989
kunstcatalogus